On a Theorem of Arrow: Comment - Arrow, Kenneth J. (Review of Economic Studies, 1975)
Journal Article On a Theorem of Arrow: Comment Get access Kenneth J. Arrow Kenneth J. Arrow Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 3, July 1975, Pages 487–488, https://doi.org/10.2307/2296863 Published: 01 July 1975